Mechanical properties and durability of recycled gold tail powder concrete - Mingxin Wang; Wenjie Zhao; Hongyi Xi; Teng Zhang; Ziyi Wang (Results in Engineering)
Gold tailings powder (GTP) is an industrial waste that is difficult to dispose of, and its accumulation has increasingly severe environmental consequences. To address the environmental pollution caused by GTP, its recycling is of significant importance for emission reduction. Therefore, this study investigates the performance deterioration patterns of GTP-based concrete under varying replacement ratios (0 %, 10 %, 20 %, and 30 %) and water-cement ratios (0.42 and 0.38) by directly replacing cement with GTP to produce low-carbon green concrete. Initially, the activity index of GTP was determined through pozzolanic activity tests, and GTP-based concrete was fabricated by direct substitution. Subsequently, mechanical performance tests (compressive, tensile, and flexural strengths), freeze-thaw damage, and dry-wet cycle tests were conducted on GTP-based concrete specimens to explore their material properties and durability. The experimental results indicate that after 200 freeze-thaw cycles, the compressive strengths of GTP-based concrete specimens with replacement ratios of 0 %, 10 %, 20 %, and 30 % decreased by 30.7 %, 33.87 %, 31.26 %, and 40.73 %, respectively, compared to undamaged specimens. After 30, 50, and 70 dry-wet cycles, the compressive strengths of GTPC specimens decreased by 3.81 %, 3.68 %, and 11.51 %, respectively, while their tensile strengths decreased by 5.57 %, 2.88 %, and 8.42 %, respectively, compared to undamaged specimens. Finally, based on the experimental results, parameters in the compressive strength calculation formula for GTP-based concrete were revised. The revised formula can accurately predict the compressive strengths of specimens with different GTP replacement ratios. The research findings provide optimal mix design recommendations for the preparation of green low-carbon concrete, contributing to reduced environmental pollution.